تحليل أنشطة المتون النحوية وتقويمها في: متن الآجرومية وملحة الإعراب والألفية ولامية الأفعال - بوعنينبة, سفيان; خنطوط, إسماعيل (جامعة الوادي - University of Eloued, 2021)
من بين المراجع التي لا تزال مُعتمَدَةً في تعليم النحو والصرف في بعض الجامعات كالأزهر، وبعض المعاهد الإسلامية والمدارس القرآنية في الجزائر، والمحاضر العلمية في موريتانيا، متن الآجرومية في النحو لابن آجروم، مع شرحه؛ التحفة السَّنِية لمحي الدين عبد الحميد، ومتن ألفية ابن مالك في النحو والصرف مع شرح ابن عقيل، ومتن ملحة الإعراب وشرحه للحريري، ومتن لامية الأفعال لابن مالك مع شرح فتح الأقفال لبحرق اليمني، فهي بالنسبة إليهم المقررات التعليمية التي تقوم عليها العملية التعليمية، وعليها المعول في تكوين جانبين مهمين من مستويات النظام اللغوي عند المتعلم، وهما المستوى التركيبي والمستوى الصرفي. وعليه آثرت تحليل محتوى هذه المقررات لإدراك مدى تحقق معياري الواقعية والبساطة فيها؛ لكونهما يتفرعان عن معيار من أهم معايير اختيار المحتوى التعليمي، وهو معيار المنفعة، الذي ترتبط أهم قواعده بالقاعدة النحوية وتطبيقاتها، لذا انطلق التحليل من الأمثلة اللغوية المتوفرة بكثرة في المستويين التركيبي والصرفي، للمتون النحوية السابقة وشروحها Among the references that are still relied upon in teaching grammar and morphology in some universities such as Al-Azhar, and some Islamic institutes and Quranic schools in Algeria, and some scientific spheres in Mauritania, Matn El Ajoromiya in grammar, written by Ibn Ajrom with his explanation; The masterpiece of Muhyi al-Din Abd al-Hamid, the text of the Alfiyyah of Ibn Malik in grammar and morphology, explained by Ibn Aqil, Milhat Al Irab text and its explanation by al-Hariri, and the text of Lamiyya al-Afaal by Ibn Malik with the explanation of Fath Al-Akfal by Buhrak al-Yamani. For them, they are the educational courses on which the educational process is based, and they depend on the formation of two important aspects of the levels of the language system for the learner, namely the structural and morphological levels. Accordingly, I analyzed the content of these because they are branched from one of the most important criteria for choosing educational content, which is the criterion of utility, the most important of which is related to the grammatical rule and its applications. So the analysis proceeded from the linguistic examples that are abundantly available at the structural and morphological levels, for the previous grammatical texts and their explanations.
Analyzing and evaluating the Activities of Grammatical Texts in: Matn al-Ajrumiyyah, Milhat Al-Irab, Alfiat Ibn Malik, and Lamiat El Afa al
مقال
Keywords: المتون؛ المقررات التعليمية؛ النظام اللغوي؛ الواقعية؛ البساطة; Contents; educational courses; linguistic system; realism; simplicity